2004
DOI: 10.5507/bp.2004.004
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Insulin Aspart vs Phosphate-Buffered Human Regular Insulin in Persons With Type 1 Diabetes Treated by Means of an Insulin Pump

Abstract: Insulin analog aspart appears to be more effective for continuous subcutaneous insulin infusion than regular human insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Insulin pumps lead not only to the improved glycemic profiles but in comparison with conventional medications, also limit the degree of hypoglycemia 23 . In our recent study we concluded that for this form of treatment, it is better to give priority to short duration insulin analogues (such as insulin aspart, Novorapid) than human insulin Actrapid 25 . This discovery is in accordance with other investigations which have confirmed the superior efficacy of the Lispro insulin analog in external pumps (Humalog) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin pumps lead not only to the improved glycemic profiles but in comparison with conventional medications, also limit the degree of hypoglycemia 23 . In our recent study we concluded that for this form of treatment, it is better to give priority to short duration insulin analogues (such as insulin aspart, Novorapid) than human insulin Actrapid 25 . This discovery is in accordance with other investigations which have confirmed the superior efficacy of the Lispro insulin analog in external pumps (Humalog) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have compared insulin aspart CSII with buffered RHI CSII, using change in HbA 1c as the outcome [ 120 122 ] (Table 3 b). Randomized trials of 7 weeks in 29 adults with T1D [ 120 ] and 16 weeks in 146 adults with T1D [ 121 ] demonstrated little change in HbA 1c from baseline and no between-treatment differences.…”
Section: Clinical Efficacy Of Insulin Aspartmentioning
confidence: 99%
“…Randomized trials of 7 weeks in 29 adults with T1D [ 120 ] and 16 weeks in 146 adults with T1D [ 121 ] demonstrated little change in HbA 1c from baseline and no between-treatment differences. In contrast, a 90-week study of 21 adults with T1D demonstrated an improvement in HbA 1c after switching from buffered RHI to treatment with insulin aspart CSII (7.89 % vs 7.53 %, respectively, p < 0.05) [ 122 ].…”
Section: Clinical Efficacy Of Insulin Aspartmentioning
confidence: 99%
“…It is now recognised that use of a rapid acting analogue in the pump, rather than regular insulin, or buffered regular insulin, can improve the effectiveness of insulin therapy. [75][76][77][78] The concern has been that use of a rapid acting analogue would result in a rapid onset of diabetic ketoacidosis in the event of pump failure. However, a paediatric trial looking at this issue did not demonstrate an increase in diabetic ketoacidosis when insulin Lispro was used in place of regular insulin.…”
Section: Clinical Utilitymentioning
confidence: 99%